PENGARUH STATUS SOSIAL EKONOMI ORANGTUA TERHADAP PRESTASI BELAJAR SISWA DI SMP MASMUR PEKANBARU - Novri Syarbaini; Swis Tantoro (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2017)
This research to know the effect social status of parent’s economics to student study achievement in Masmur Junior high school at Pekanbaru. This research location in Masmur Junior high school at Pekanbaru. This research start from on April until November 2016. The variants of research is quantitative descriptive research. The data from this research to get validity and reliability data account technique is using sampling technique and sample used 25 people. Result of research is status social of parent’s economics give the effect significant to student study achievement in Masmur Junior high school at Pekanbaru. Because student from social status of high parent’s economics will enough need,their study and high study achievement. And student from low social status of parent’s economics nothing high in study achievement.Keywords : status social economics and study achievement